2012
DOI: 10.1016/s0034-7094(12)70176-9
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Anesthesia with Low-Dose Bupivacaine-Fentanyl Combination: A Good Alternative for Day Case Transurethral Resection of Prostrate Surgery in Geriatric Patients

Abstract: Intrathecal 4 mg bupivacaine + 25 μg fentanyl provided adequate spinal anesthesia with shorter block duration and postanesthesia care unit stay with stable hemodynamic profile than intrathecal 50 mg prilocaine + 25 μg fentanyl for day case transurethral resection of prostate surgery in geriatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…In geriatric patients undergoing day-case transurethral resection of the prostate (TURP) surgery, Akcaboy matched intrathecal administration of a conventional dose of 50 mg 2% hyperbaric prilocaine plus fentanyl 25 μg and a low dose of 4 mg 0.5% hyperbaric bupivacaine plus fentanyl 25 μg 37. Dermatome T10 was the desired level of analgesia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In geriatric patients undergoing day-case transurethral resection of the prostate (TURP) surgery, Akcaboy matched intrathecal administration of a conventional dose of 50 mg 2% hyperbaric prilocaine plus fentanyl 25 μg and a low dose of 4 mg 0.5% hyperbaric bupivacaine plus fentanyl 25 μg 37. Dermatome T10 was the desired level of analgesia.…”
Section: Resultsmentioning
confidence: 99%
“…Although the combination of prilocaine and fentanyl (20–25 μg) has been tested with the aim to improve the quality and extend the duration of the spinal block, pruritus and urinary retention are possible side effects which can delay home discharge 29,36,37…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43] Given the increasing proportion of anesthesia administered in the ambulatory setting, 44,45 there is demand for anesthetic techniques which allow for rapid recovery with minimal side effects. 46,47 The demand for low-dose spinal techniques in ambulatory surgery highlights the need for additional studies focusing on nonobstetric populations.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperbaric prilocaine provides faster spinal block onset and earlier patient recovery in ambulatory surgery compared to plain prilocaine [ 14 ]. Plain prilocaine was also compared to bupivacaine in day-case surgery and the authors concluded that bupivacaine provided shorter block duration [ 15 ]. The baricity of the local anaesthetic agent is the major factor that influences the distribution of the local anaesthetic in the subarachnoid space [ 16 ].…”
Section: Introductionmentioning
confidence: 99%